Comparison of Short Acting versus Long Acting Filgrastim for Reduction of Chemotherapy Induced Febrile Neutropenia - Sharma, Rajeev; Shilpakar, Ramila; Thapa, Sudip; K.C., Anuj; Dulal, Soniya; Prajapati, Roshan; Acharya, Bibek; Chapagain, Sandhya; Paudel, Saugat; Paudel, Bishal; Pokhrel, Samikcha; Dutta Paudel, Bishnu (Annapurna Journal of Health Sciences, 2023)
Introduction: Febrile neutropenia (FN) is the most frequent complications reported during cytotoxic chemotherapy treatment. Granulocyte colony stimulating factor (GCSF) is used to reduce neutropenia and related complications. This study compares short versus long acting filgrastim for reduction of chemotherapy induced FN. Methods: Histologically confirmed solid cancer patients (n=112) receiving either high risk or intermediate risk chemotherapy regimens for FN were randomized into two groups. Group one received filgrastim 300 mcg subcutaneously for five days and group two received pegfilgrastim 6 mg subcutaneously single dose, starting after 24 hours after completion of chemotherapy during each chemotherapy cycle. The primary end point was the occurrence of FN. The secondary end points were number of hospital visits, duration of hospital stay and total direct costs of filgrastim and pegfilgrastim. Results: Fifty six patients were analyzed in each group. The incidence of FN was significantly lower in pegfilgrastim group (42.90%) than filgrastim group (69.6%), p<0.004. The mean hospital visits were 1.84±1.93 in filgrastim group and 0.84±1.19 in pegfilgrastim group with 58.90% and 33.90% hospital admission respectively in both groups. The mean duration of stay was 4.14±3.69 days in filgrastim group and 2.36±3.35 days in pegfilgrastim group. The mean cost (Nepali rupees) of filgrastim and pegfilgrastim was 20162.50+6645.37 (US168.17±55.42) and 32210.71±10429.43(268.67±86.99) respectively. Conclusion: Single dose of pegfilgrastim was significantly better than multiple doses of filgrastim for reducing FN incidence in cancer patients receiving chemotherapy